Protective effect of Citrus macroptera fruit pulp juice rendering Nrf2-pathway against cisplatin-induced genotoxicity - Md. Mahmudul Hasan, Rubait Hasan, Md. Rezuan Al Mahmud, Md. Gaziul Islam (Journal of Applied Pharmaceutical Science, 2018)
Citrus macroptera (Rutaceae) has long been used as an appetite stimulant and in the treatment of fever. Protective effect of C. macroptera against oxidative stress has studied but there is a lack of information concerning its role in antioxidant-related gene expression. Thus, this study was particularly aimed to investigate the protective effect of C. macroptera fruit pulp juice (CMFPJ) in anticancer drug cisplatin (CP)-induced genotoxicity. Male albino mice were treated with 2.5 mg/kg CP (CP 2.5) for five consecutive days. Recovery from genotoxicity was carried out by treating mice with 25 and 50 mg/kg CMFPJ for the next five consecutive days and treatments were given intraperitoneally (ip). The animals were sacrificed and polychromatic erythrocytes (PCE) with micronuclei (MN), the percentage of PCE, and sperm morphology were studied. In addition, the expression of nicotinamide adenine dinucleotide phosphate hydrogen (NADPH) quinone oxidoreductase 1 (NQO1); an antioxidant gene responsible for producing an enzyme that detoxifies chemical stressors was analyzed. CMFPJ significantly decreased (p < 0.05) MN in PCE, % of PCE, and sperm abnormalities. Besides, CMFPJ induced the expression of NQO1. The polyphenol, flavonoids, and vitamin-C present in CMFPJ synergistically showed the protective effect against CP-induced genotoxicity.
Keywords: Cisplatin, oxidative stress,Citrus macroptera, NQO1,polychromatic erythrocytes,sperm morphology.